Ultra-low-loss interconnection between dielectric and planar transmission line technologies for millimeter-wave applications - Dorbath, Benedikt; Distler, Felix; Schur, Jan; Vossiek, Martin (GeMIC 2020 - Proceedings of the 2020 German Microwave Conference, 2020)
Key future applications, such as multi-gigabit communication, multiple-input multiple-output (MIMO) technologies and networked radars for autonomous driving, require broadband, low loss, lightweight millimeter-wave and THz transmission lines to interconnect circuits, components, modules and systems. Dielectric waveguides (DWG) have proven to be an attractive transmission line option, because they can meet these requirements. Apart from a decent DWG performance, the transition between DWGs and printed circuit boards (PCB) is key to a successful application of DWG technology in particular for monolithic microwave integrated circuit (MMIC) based millimeter-wave systems. In this paper, a waveguide transition between a polarization stable rectangular DWG and a microstrip line (MSL) for W-Band is presented. The design of the waveguide transition aims to minimize the insertion loss considering the constraints of the given manufacturing specifications. A transition with an insertion loss of less than 1.2dB from 82GHz to 94.5GHz is achieved by using an insertion loss simulation model and evaluated by measurements from a fabricated back-to-back transition test setup.
CRIS-Team Scopus Importer:2020-06-02
Keywords: dielectric waveguide; double ridge waveguide; interconnection; microstrip line; waveguide transition